Wieloletnie planowanie inwestycyjne i finansowe w systemie zarządzania gminą - Świderska, Joanna; Żuk, Krzysztof (Long-Term Investment and Financial Planning in the System of Commune Management, 2007)
The combination of long-term investment planning with financial planning enhances the rationalization of investment expenditures and improves the effectiveness of local budget policy. Preferential credits and loans, and then commercial credits, remain the main repayable source of investments financing. Also structural funds are increasingly used, and therefore, the time scope of long-term investment plans should be correlated with the system of long-term planning existing in the EU. However, for the reason of attractiveness, the issuance of municipal bonds should be used to a larger extent. It becomes especially important in the context of execution of long-term investment strategies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 679-689